The first study to evaluate non-invasive haemodynamic profile changes in reaction to nitroglycerin in patients with HFmrEF in comparison to HFpEF and HFrEF. (3rd October 2022) - Morawiec, R; Drozdz, J
Abstract: Introduction: According to 2021 guidelines for management of heart failure (HF) there are 3 types of HF – with reduced (HFrEF; ≤40%), mildly reduced (HFmrEF; 41–49%) and preserved (HFpEF; ≥50%) left ventricle ejection fraction (LVEF). The middle group – HFmrEF – is the least known and requires further research. The aim of the study was to assess clinical and hemodynamic profile of patients with HFmrEF at rest and after sublingual administration of 0.4 mg of nitroglycerin (NTG). Material and methods: The hemodynamic profile was assessed on the last day of hospitalization due to acute decompensated heart failure. The control groups for patients with HFmrEF were groups of HFpEF and HFrEF, while there was no control group on healthy subjects. The clinical profile of patients was assessed by data from medical interview, results of laboratory tests and measured echocardiographic parameters, while the hemodynamic profile – at rest and after administration of 0.4mg of NTG – was assessed by electrical cardiometry (EC) using the ICON® device. Results: Overall, 15 consecutive patients from each type of HF were included into the study and most of them were men (N=32; 71%). Diabetes was significantly more frequent in the HFpEF group. The HFrEF group had significantly higher left ventricle end-diastolic dimension (LVDD; p=0.0003) and lower right ventricle systolic function (TAPSE; p=0.0026). The analysis of the hemodynamic profile at rest showed significant differences between HFmrEF and HFrEF in systolic time ratio (STR; p=0.0202) and pre-ejection period (PEP; p=0.0487). In comparison to HFrEF group, patients with HFmrEF were significantly different in the change of stroke volume and stroke volume index (SV/SI; p=0.0134/0.0223), cardiac output and cardiac index (CO/CI; p=0.005/0.0079), systemic vascular resistance and its' indexed values (SVR/SVRI; p=0.0339/0.0294), the cardiac power index (CPI; p=0.0489) and corrected flow time (FTC; p=0.0369). The change in the following parameters: SV, SI, CO, CI, FTC, SVR, SVRI and CPI after NTG administration, in the HFmrEF group had and an opposite direction in comparison to patients with HFpEF (p=NS) and HFrEF (p<0.05) (Fig. 1). The principal component analysis showed that the HFmrEF group is less heterogenetic and located within the two others (Fig. 2). Conclusions: Clinical profile of patients with HFmrEF based on medical interview, laboratory and echographic findings showed that they are a mid-filed group. Patients with HFmrEF significantly differs from HFrEF in the changes of hemodynamic profile after sublingual NTG administration, considering EC parameters of the blood flow (SV, SI, CO, CI, SVR, SVRI) and heart muscle contractility (CPI, FTC). The reaction to NTG showed that HFmrEF is the intermediate and more homogeneous group that is comprised in the other two groups. The median reaction to NTG in the HFmrEF group was opposite to the reaction in HFpEF and HFrEF patients. Funding Acknowledgement: Type of funding sources: None.